DEVELOPING THE PROFESSIONAL COMPETENCE OF FUTURE PRIMARY EDUCATION TEACHERS THROUGH ARTIFICIAL INTELLIGENCE TECHNOLOGIES (Web of Teachers: Inderscience Research, 2023)
This article analyzes the development of professional competence of future primary education teachers through artificial intelligence technologies. It substantiates the relevance of this issue in the context of digital transformation, clarifies the structure of professional competence, and highlights the pedagogical potential of AI tools. Based on competency-based and system-activity approaches, a conceptual model is proposed. The study uses theoretical analysis and pedagogical modeling. The results indicate that integrating AI technologies enhances pedagogical, methodological, digital, and reflective competencies. These findings can be applied in higher pedagogical education to improve teacher training quality and ensure more effective professional preparation in modern educational environments.